Risks and contraindications of medical compression treatment – A critical reappraisal. An international consensus statement. (August 2020) - Rabe, Eberhard; Partsch, Hugo; Morrison, Nick; Meissner, Mark H; Mosti, Giovanni; Lattimer, Christopher R; Carpentier, Patrick H; Gaillard, Sylvain; Jünger, Michael; Urbanek, Tomasz; Hafner, Juerg; Patel, Malay; et al.
Objectives: Medical compression therapy is used for non-invasive treatment of venous and lymphatic diseases. Medical compression therapy-associated adverse events and contraindications have been reported, although some contraindications are theoretically based. This consensus statement provides recommendations on medical compression therapy risks and contraindications. Methods: A systematic literature search of medical compression therapy publications reporting adverse events up until November 2017 was performed. A consensus panel comprising 15 international experts critically reviewed the publications and formulated the recommendations. Results: Sixty-two publications reporting medical compression therapy adverse events were identified. The consensus panel issued 21 recommendations on medical compression therapy contraindications and adverse event risk mitigation, in addition to reviewing medical compression therapy use in borderline indications. The most frequently reported non-severe medical compression therapy-associated adverse events included skin irritation, discomfort and pain. Very rare but severe adverse events, including soft tissue and nerve injury, were also identified. Conclusion: This consensus statement summarises published medical compression therapy-associated adverse events and contraindications, and provides guidance on medical compression therapy. Severe medical compression therapy-associated adverse events are very rarely encountered if compression is used correctly and contraindications are considered.